2016
DOI: 10.1016/j.jiph.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

WHO Safety Surgical Checklist implementation evaluation in public hospitals in the Brazilian Federal District

Abstract: The World Health Organization (WHO) created the WHO Surgical Safety Checklist to prevent adverse events in operating rooms. The aim of this study was to analyze WHO checklist implementation in three operating rooms of public hospitals in the Brazilian Federal District. A prospective cross-sectional study was performed with pre- (Period I) and post (Period II)-checklist intervention evaluations. A total of 1141 patients and 1052 patients were studied in Periods I and II for a total of 2193 patients. Period I to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 21 publications
0
26
0
16
Order By: Relevance
“…Although studies show that the use of checklist makes the communicative process more effective in OR, the practice of nonverbal verification refers to the insufficiency in the interdisciplinary communication in OR (3,6) . The team discussions ensure greater patient safety, since professionals explain relevant topics about the client and the surgical planning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although studies show that the use of checklist makes the communicative process more effective in OR, the practice of nonverbal verification refers to the insufficiency in the interdisciplinary communication in OR (3,6) . The team discussions ensure greater patient safety, since professionals explain relevant topics about the client and the surgical planning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was concerned with reducing the Hawthorne, effect which gives greater reliability to the results obtained. In other studies of compliance in the checklist application, the team knew that it was being observed and changes in behavior may influence the assessment (3,7) .…”
Section: Counting Of Gauzes and Compressesmentioning
confidence: 99%
See 2 more Smart Citations
“…Muitas vezes, a equipe não adere ao protocolo devido à falta de percepção da importância do checklist na prática cirúrgica. Nesse sentido, o conhecimento da equipe de cirurgia é fundamental para que o protocolo seja implementado de forma adequada e homogênea, sobretudo que seja efetivamente utilizado, o que nem sempre é observado na prática, seja pelo desconhecimento ou pela falta de divulgação quanto à sua importância (11)(12)(13) . É importante ressaltar que o cumprimento desse protocolo tem como princípio fundamental a melhoria da comunicação entre os membros da equipe cirúrgica, atentando ao fato de que os eventos adversos são na maioria das vezes evitáveis.…”
Section: Introductionunclassified